Fast-dissolving antioxidant nanofibers based on Spirulina protein concentrate and gelatin developed using needleless electrospinning. (June 2022) - Mosayebi, Vahid; Fathi, Milad; Shahedi, Mohammad; Soltanizadeh, Nafiseh; Emam-Djomeh, Zahra
Abstract: Spirulina is a microalga that is well-known for its high protein content and biological activities directly related to its antioxidant capacity. The objective of this study was to produce fast-dissolving antioxidant nanofibers based on Spirulina protein concentrate (SPC) and gelatin using needleless electrospinning technique. The effect of mixing ratios of SPC (10% w/w) and gelatin (20% w/w) on the viscosity, electrical conductivity and surface tension of electrospinning solutions as well as diameter and morphology of resulting nanofibers was investigated. Increasing the SPC level in the solution blends resulted in a decrease in apparent viscosity and electrical conductivity and an almost stable trend in surface tension (29.25–32.19 mN/m) that led to diminish of diameter of the nanofibers. Scanning electron microscopy images showed that SPC/gelatin ratio of 40:60 led to the production of uniform and bead-free nanofibers with a relatively smaller average diameter (208.7 ± 46.5 nm). Atomic force microscopy images indicated mesh-like, fibrillary, and bead-free structures. Fourier transform infrared spectroscopy verified the formation of composite nanofibers and intermolecular interactions between both proteins. X-ray diffraction and thermal analysis showed higher amorphous structure and stability of produced SPC/gelatin nanofibers in comparison to pure materials which was favorable for formation of stable fast-dissolving fibers. Results of DPPH and ABTS radical scavenging activities showed that the antioxidant activity of composite nanofibers significantly improved with increasing SPC mixing ratio ( p  < 0.05). The dissolution test demonstrated that SPC/gelatin nanofibers can be rapidly dissolved in aqueous medium within 2 s. Finally, the results indicated that the electrospun SPC/gelatin nanofibers could be potentially used for nutraceutical delivery in food and packaging applications under high humidity. Graphical abstract: Image 1 Highlights: Spirulina protein concentrate/gelatin composite nanofibers were successfully fabricated via needleless electrospinning. The composite nanofibers exhibited better antioxidant activity compared to pure gelatin nanofibers. Electrospun nanofibers showed ultrafast dissolving characteristic in aqueous medium.